A MINI REVIEW ON NUTRACEUTICALS: AN EMERGING ERA IN THE HEALTH INDUSTRY - Hari, Oorvashree; Gujadhur, Medha; Moudgil, Khayati (Bangladesh Journal of Multidisciplinary Scientific Research, 2021)
Nutraceuticals have a wide range of biochemical effects on the health of consumers. The upper limit of the physiological effect dimension will be food capable of curing or healing certain ailments. Nutraceuticals also provide benefits that go beyond their fundamental nutritional functions. It is important to differentiate dietary deficiency from other physiological effects such as risk reduction for disease. Nutraceuticals include dietary supplements, genetically modified foods, herbal supplements, and refined foods. This article discusses nutraceuticals, their categories, as well as their international and national status, need protection, merits, the current nutraceutical products, major nutraceutical firms, and therapeutic applications. It also emphasizes the critical need for research and development in the formulation of nutraceuticals.